2011
DOI: 10.2967/jnumed.110.085993
|View full text |Cite
|
Sign up to set email alerts
|

Stable Delineation of the Ischemic Area by the PET Perfusion Tracer 18F-Fluorobenzyl Triphenyl Phosphonium After Transient Coronary Occlusion

Abstract: 18 F-fluorobenzyl triphenyl phosphonium (FBnTP) has recently been introduced as a myocardial perfusion PET agent. We used a rat model of transient coronary occlusion to determine the stability of the perfusion defect size over time and the magnitude of redistribution. Methods: Wistar rats (n 5 15) underwent thoracotomy and 2-min occlusion of the left coronary artery (LCA), followed by reperfusion. During occlusion, 18 F-FBnTP (92.5 MBq) and 201 Tl-thallium chloride (0.74 MBq) were injected intravenously. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 18 publications
0
56
0
Order By: Relevance
“…7,8 To address this need, we have developed 18 Figure 2A,B. In normal rats, microPET imaging demonstrated intense, homogeneous uptake of [ 18 F]FPTP through the myocardium and excellent myocardium-to-liver and myocardium-to-lung contrast 10 min after tracer injection.…”
mentioning
confidence: 99%
“…7,8 To address this need, we have developed 18 Figure 2A,B. In normal rats, microPET imaging demonstrated intense, homogeneous uptake of [ 18 F]FPTP through the myocardium and excellent myocardium-to-liver and myocardium-to-lung contrast 10 min after tracer injection.…”
mentioning
confidence: 99%
“…A full 82 Rb 3D PET scan implies an exposure of ≈ 4.3 mSv, while for a single 13 N-ammonia 3D scan, the estimated the radiation dose is around 1, and 0.8 mSv for 15 O-H 2 O [9]. The calculated exposure for 18 F-flurpiridaz has initially been estimated in 6.3 mSv [7].…”
Section: Dosimetrymentioning
confidence: 99%
“…Another major study, the PACIFIC trial, demonstrated directly that 15 O-H 2 O PET conveys the best diagnostic performance (in comparison to SPECT and CCTA) with a sensitivity of 87% and a specificity of 84% for the detection of functionally significant lesions evaluated by fractional flow reserve (FFR) [30], the current gold standard for the functional assessment of coronary stenosis [31]. Figure 3 depicts a typical patient with intermediate risk of CAD investigated for myocardial ischemia.…”
Section: Identifying and Characterizing The Burden Of Coronary Arterymentioning
confidence: 99%
See 2 more Smart Citations